Bipolar I disorder in remission vs. schizophrenia in remission: Is there a difference in burden? (2017)
Introduction: Bipolar disorder (BD) is considered to have a better outcome in comparison to schizophrenia. However, recent data dispute this notion. The current study aimed to compare the burden of patients with BD type I (BD-I) in remission with similar patients with schizophrenia (SZ) in remission. Material and Methods: Patients with schizophrenia (n=75) and BD-I (n=54) aged 18-64 years were included in the study. The diagnosis was made with the SCID-I/P. Patients were assessed for sociodemographic variables, stigma, quality of life, disability, suicidality and current symptomatology. The statistical analysis included Analysis of Covariance (ANCOVA) and chi-square test. Results: ANCOVA with age at onset as a covariate and marital status and diagnosis as grouping variables returned no significant difference. Discussion: The results of the current study suggest that when in remission, BD-I patients do not differ from patients with schizophrenia with regards to stigma, quality of life, disability level and suicidality. Also, when in remission, they do not differ regarding the severity of their psychopathology.